The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.9734/indj/2021/v16i330183
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Internet Addiction among Clinical Medical Students of a Nigerian Private University

Abstract: Aim: This study aimed to determine the prevalence and associated factors of internet addiction among undergraduate clinical medical students of a Nigerian private university. Study Design: Cross sectional descriptive study Place and Duration of Study: College of Medicine and Allied Health Sciences, Bingham University, Jos campus, Plateau state, Nigeria, between May and July 2021. Methods: We included 383 (147 males and 236 females, age range 18 – 49 years) clinical medical students of Bingham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Additional sleep quality dysfunctions affected positively by IA included daytime sleeping (Citil et al, 2022;Demir et al, 2020), daytime dysfunction (Ayran et al, 2019;Lin et al, 2019), use of sleep medication (Ayran et al, 2019;Lin et al, 2019), sleep latency (Ayran et al, 2019;Lin et al, 2019). Also, IA was similarly affected by sleepless nights or problems sleeping (Ihekaike et al, 2021;Lin et al, 2019;Sharma et al, 2014) and sleep deprivation (Li et al, 2015). However, few studies reported no significant direct effect of IA on poor sleep quality (You et al, 2021;Zhang, Wu, 2020) and insomnia (Obiagaeri, Chidozie, 2020).…”
Section: Internet Addiction and Sleep Problemsmentioning
confidence: 99%
“…Additional sleep quality dysfunctions affected positively by IA included daytime sleeping (Citil et al, 2022;Demir et al, 2020), daytime dysfunction (Ayran et al, 2019;Lin et al, 2019), use of sleep medication (Ayran et al, 2019;Lin et al, 2019), sleep latency (Ayran et al, 2019;Lin et al, 2019). Also, IA was similarly affected by sleepless nights or problems sleeping (Ihekaike et al, 2021;Lin et al, 2019;Sharma et al, 2014) and sleep deprivation (Li et al, 2015). However, few studies reported no significant direct effect of IA on poor sleep quality (You et al, 2021;Zhang, Wu, 2020) and insomnia (Obiagaeri, Chidozie, 2020).…”
Section: Internet Addiction and Sleep Problemsmentioning
confidence: 99%